1984
DOI: 10.3109/10915818409009078
|View full text |Cite
|
Sign up to set email alerts
|

A Chronic Inhalation Study with Unleaded Gasoline Vapor

Abstract: A chronic inhalation study of unleaded gasoline vapor was conducted in mice and rats. The gasoline employed was typical of gasoline used in the US and contained 2% benzene. Groups of both sexes of B6C3F1 mice and Fischer 344 rats were exposed to three concentrations of vapor, 67, 292, and 2056 ppm. Exposures were for 6 hours per day, 5 days per week, for periods ranging from 103 to 113 weeks. Interim sacrifices were conducted at 3, 6, 12, and 18 months. Laboratory studies, including hematological and biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…However, overall combination of incidence and severity of the lesion, assessed using the Kolmogorov–Smirnoff test, was significantly greater in the mid- and high-level exposure groups. This finding in males is consistent with male-rat-specific light hydrocarbon-induced alpha-2μ globulin overload nephropathy that was reported previously in studies with wholly vaporized unleaded gasoline ( MacFarland et al, 1984 ). In F344 male rats, after approximately 1 yr of age, alpha-2μ globulin overload nephropathy is essentially masked by age-related chronic progressive nephropathy, since both forms of nephropathy share similar if not identical diagnostic hallmarks.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…However, overall combination of incidence and severity of the lesion, assessed using the Kolmogorov–Smirnoff test, was significantly greater in the mid- and high-level exposure groups. This finding in males is consistent with male-rat-specific light hydrocarbon-induced alpha-2μ globulin overload nephropathy that was reported previously in studies with wholly vaporized unleaded gasoline ( MacFarland et al, 1984 ). In F344 male rats, after approximately 1 yr of age, alpha-2μ globulin overload nephropathy is essentially masked by age-related chronic progressive nephropathy, since both forms of nephropathy share similar if not identical diagnostic hallmarks.…”
Section: Resultssupporting
confidence: 92%
“…The control incidence in the parallel GVC study was 4/40 (8%). Additionally, increases in this neoplasm have not been observed in previous studies with neat MTBE or wholly vaporized gasoline ( Cruzan et al, 2007 ; MacFarland et al, 1984 ). Therefore, it is judged unlikely that the increased incidence in female mammary-gland fibroadenoma was treatment-related.…”
Section: Resultsmentioning
confidence: 53%
See 1 more Smart Citation
“…But recent reviews of cohort studies found little or no evidence of an excess risk of kidney cancer 46,47 . Gasoline came under suspicion as a risk factor for renal cell cancer when male rats exposed long-term to vapors of unleaded gasoline developed a signifi cant excess of renal cancers 48 . A number of epidemiological studies have examined the eff ect of gasoline exposure with inconsistent results 42,[49][50][51] .…”
Section: Gasoline and Other Petroleum Productsmentioning
confidence: 99%
“…A chronic inhalation study has shown that unleaded gasoline vapor caused kidney carcinomas and sarcomas in male rats with some evidence of a dose-response relationship (1). Also observed was an increase in liver masses and modules in female mice.…”
mentioning
confidence: 99%